The Influence of the Project Based Learning Model on Creative Thinking Skills Students of Karangjati 01 Elementary School, Cilacap through Ecoprinting - Wahyu Sagita Eka Cahyani; Ristiana Dyah Purwandari (UM Purwokerto Press, 2025)
This study aims to analyze the effect of the Project-Based Learning (PjBL) learning model on students' creative thinking skills at SDN Karangjati 01 Cilacap through ecoprint making. This study uses a qualitative approach with a descriptive method. Data were collected through observation and interviews during the learning process. The subjects of the study were 23 fifth-grade students of SDN Karangjati 01 Cilacap who participated in learning with the PjBL model. The results showed that the PjBL learning model that integrated ecoprint making activities had a positive effect on students' creative thinking skills. Students were more active, innovative, and able to produce creative ecoprint works. The application of the PjBL model also increased student motivation and participation in learning. Thus, the PjBL learning model through ecoprint making is effective in improving students' creative thinking skills in elementary schools.